Use of the Coyol Palm (Acrocomia aculeata) for the Production of “Taberna,” a Traditional Fermented Beverage in México - Ambrocio-Ríos, José A.; Orantes-García, Carolina; Sánchez-Cortés, María S.; Verdugo-Valdez, Alma G. (Frontiers in Sustainable Food Systems, 2021)
Acrocomia aculeata is a palm, which is used for various purposes in different rural communities in southeastern Mexico; among which is the obtaining of a traditional fermented beverage called “taberna.” The objective of this study was to know the management that taberna producers give to the coyol palm. The work was carried out between march and april 2016 in two communities in Chiapas. The information on palm management was obtained by applying semi-structured interviews to the families that make the beverage in each community, who narrated the process of using the palm; from its care in the field, to its court for the elaboration of a taberna and the uses and customs that revolve around this activity were described. With this work, it was possible to know the details of the elaboration of the beverage from a social and cultural perspective, which is surrounded by traditional knowledge, with great biocultural importance that gives identity not only to the communities that possess the resource, but also to the families that they take advantage of it. With this, it is expected to contribute to a management and conservation plan for the species, to guarantee the resource to the communities and preserve the biological and cultural diversity associated with this activity, given that the use of natural resources is ultimately a biocultural heritage that implies a relationship between natural resources, people, regions and local culture.